IN VITRO CIPROFLOXACIN RESISTANCE PATTERNS OF GRAMPOSITIVE BACTERIA ISOLATED FROM CLINICAL SPECIMENS IN A TEACHING HOSPITAL IN SAUDI ARABIA - Akhtar, Naeem; Alzahrani, Alhusain; Obeid, Obeid El-Treify; Dassal, Dennis (Journal of Ayub Medical College Abbottabad, 2009)
Background: Over the last few decades the ever-increasing level of bacterial resistance to antimicrobials has been a cause of worldwide concern. Fluoroquinolones, particularly ciprofloxacin has been used indiscriminately for both gram-positive and gram-negative bacterial infections. The increased use of ciprofloxacin has led to a progressive loss of bacterialsusceptibility to this antibiotic. Therefore it is necessary to have update knowledge of resistance pattern of bacteria to this antibiotic so that alternate appropriate antibiotics can be used for ciprofloxacin-resistant bacterial infections. Objective: To evaluate the trends of ciprofloxacin resistance pattern in commonly isolated grampositive bacteria over time in a Saudi Arabian teaching hospital. Methods: A retrospective analysis was carried out for ciprofloxacin susceptibility patterns of 5534 isolates of gram-positive bacteria isolated from clinical specimens submitted to microbiology laboratories at King Fahd Hospital of the University (KFHU), Al-Khobar, Saudi Arabia during the period from January 2002 to August 2005. Results: Increase in ciprofloxacin resistance rates with some fluctuations, among these isolates, were observed. For Staphylococcus aureus, it varied from 4.62, 1.83, 7.01 and 3.98%, methicillin resistant Staphylococcus aureus (MRSA) 97.92, 97.75, 87.01 and 88.26%, Streptococcus pyogenes 5.35, 4.47, 14.44 and 3.53% during the years 2002, 2003, 2004 and 2005 respectively. Cirprofloxacin resistance during the years 2002, 2004 and 2005 for other isolates was as follows: Streptococcus pneumoniae, 30.23, 23.02 and 26.47%; enterococcus group D, 43.05, 20.68 and 57.03% and non-enterococcus group D, 62.96, 76.92 and 87.50% respectively. Conclusion: Ciprofloxacin resistance in grampositive bacterial clinical isolates particularly Staphylococcus aureus, methicillin resistant Staphylococcus aureus (MRSA) enterococcus group D, and non-enterococcus group D, has greatly increased and ciprofloxacin no more remains the drug of choice for these infections. Keywords: Ciprofloxacin, Antibiotic resistance, Staphylococci, Streptococcus pyogenes, Streptococcus pneumoniae, Enterococci